2017
DOI: 10.18203/2394-6040.ijcmph20173836
|View full text |Cite
|
Sign up to set email alerts
|

A study on prevalence of obesity and life-style behaviour among medical students

Abstract: INTRODUCTIONThe incidence of obesity is increasing dramatically worldwide. Overall 23% world adult population is overweight and 9.8% obese. By 2030, the number of overweight and obese adults is projected to be 2.16 and 1.12 billion, (38% and 20%), respectively. 1 Overweight/obesity is the fifth leading risk factor for global death. At least 2-8 million adults die each year as a result of being overweight or obese.2 A variety of factors including faulty diet, genetic predisposition, physical inactivity and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
2
2
1
Order By: Relevance
“…This is consistent with study findings conducted on medical students in Malaysia, 15 India, 11 and in Pakistan. 20 On the contrary, the findings of our study contradicted the findings of two studies conducted by Anupama 21 and Fernandez, 22 which showed that the predominant proportion of their medical students who have higher BMI overtime is female. All the above mentioned studies were conducted through cross-sectional study design where there is generally no evidence of the temporal relationship between the variables and BMI, thus could not establish causality.…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with study findings conducted on medical students in Malaysia, 15 India, 11 and in Pakistan. 20 On the contrary, the findings of our study contradicted the findings of two studies conducted by Anupama 21 and Fernandez, 22 which showed that the predominant proportion of their medical students who have higher BMI overtime is female. All the above mentioned studies were conducted through cross-sectional study design where there is generally no evidence of the temporal relationship between the variables and BMI, thus could not establish causality.…”
Section: Discussioncontrasting
confidence: 99%
“…From our study, it can be observed that there is a significant association between overweight and obesity and the habit of taking breakfast daily (P=0.001). Studies conducted by Deotale et al, 11 and Anupama et al, 12 concluded that there is a significant association between skipping breakfast and overweight and obesity, which was similar to our study. In contrast, a study conducted by Veena et al, 23 concluded that skipping breakfast was not associated with obesity.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of the students, 250 (96.15%), were hostellers, whereas 10 (3.85%) were day scholars. Similar to our study, Anupama et al, 12 and Deotale et al, 11 observed that a sizable portion of the participants were residing in hostel facilities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3 Ma et al found that breakfast skipping adults and adolescents tend to eat more for the rest of the day 33 hence being obese. 34 As breakfast skipping increases appetite and diminish satiety, it is associated with more energy consumption during later meals with poor food quality. The hunger aroused by skipping breakfast could shift the food choices also at subsequent meals toward energy and fat-dense foods.…”
Section: Discussionmentioning
confidence: 99%